Role of ultrasound elastography in the evaluation of rotator cuff tendon in patients with shoulder pain and its comparison with magnetic resonance imaging - Vaibhav Goyal,; Ankur Malhotra,; Shruti Chandak,; Deepti Arora,; Arpit Deriya,; Shweta Kataria,; Sunil Kumar, (Asian Journal of Medical Sciences, 2023)
Background: Pain in the shoulder is the third-most prevalent musculoskeletal pain type. Most frequently involved in tendinopathy/tendon tears is the supraspinatus tendon, followed by a combination of the supraspinatus and infraspinatus tendon. At present, gray-scale ultrasound and MRI are used to determine the tear size, gross morphology, and postsurgical tendon repair. However, they are unable to determine the material characteristics of the muscle or tendon. Aims and Objectives: The aim of this study is to assess the role of ultrasound elastography in the evaluation of the rotator cuff tendon and to compare gray scale ultrasound and shear wave elastography (SWE) findings of the supraspinatus tendon with MRI in patients with shoulder pain. Materials and Methods: This prospective observational study included 50 patients. They were examined using a 1.5-T MRI machine and the ACUSON S3000 (Siemens Medical Solution) machine. The radiologist performing the ultrasound was blinded by the results of the MRI. Results: Age varied from 19 to 75 years. The majority (34%) were in the range of 31–40 years. Males were predominately affected. In MRI, the most common type of injury was mild tendinosis (34%), followed by moderate/severe tendinosis (26%). About 30% were diagnosed with moderate/severe tendinosis, 24% with mild tendinosis, 22% with partial tears, and 18% with full-thickness tears in gray-scale ultrasound. When SWE was combined, 32% were diagnosed with moderate/severe tendinosis, 28% with mild tendinosis, 20% with a partial tear, and 14% with a full-thickness tear. Conclusion: SWE showed better diagnostic performance than gray-scale ultrasound in the detection of supraspinatus tendinopathy.